2018
DOI: 10.1002/hep.29901
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate pediatric acute liver failure is uniquely characterized by a CD103+CD8+ T‐cell infiltrate

Abstract: Indeterminate PALF is characterized by a dense CD8 T-cell hepatic infiltrate consistent with expansion of a tissue resident memory T-cell phenotype; CD8 T-cells are a biomarker of immune dysregulation in iPALF and may be used to better identify and define this group. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 35 publications
5
54
1
Order By: Relevance
“…In this study, we confirm in all the sHLH or MAS patient livers analysed the infiltration from CD8-positive T cells. Interestingly, biopsies from children with acute liver failure of unknown causes are characterized by a dense infiltrate of perforin expressing CD8-positive T cells [19]. Infiltration from CD8-positive T cells has been proposed as a biomarker able to differentiate acute liver failure of unknown causes from acute liver failure with known aetiology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirm in all the sHLH or MAS patient livers analysed the infiltration from CD8-positive T cells. Interestingly, biopsies from children with acute liver failure of unknown causes are characterized by a dense infiltrate of perforin expressing CD8-positive T cells [19]. Infiltration from CD8-positive T cells has been proposed as a biomarker able to differentiate acute liver failure of unknown causes from acute liver failure with known aetiology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of liver T RM cells under nonimmunized or uninfected conditions has not been elucidated. It was recently reported that CD8 + T cells with T RM ‐like features are accumulated in liver of iPALF patients, suggesting that liver CD8 + T RM cells might be involved in the immunopathogenesis that leads to liver failure. On the other hand, the CD8 + T RM cell population was also expanded in livers of Cic f/f ;Vav1‐Cre mice (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although hepatic CD8 + T RM cells are known to contribute to protective immunity against liver‐stage malarial infection, it has not been appreciated how important the maintenance of the CD8 + T RM cell population at physiological levels is. Moreover, although it was observed that frequency of CD8 + T RM ‐like cells are increased in liver of iPALF patients, it remains unclear that this causes liver failure. Our study suggests that enhanced formation of liver CD8 + T RM cells is detrimental to the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, an inverse correlation between liver T RM frequencies and viral titers was observed, indicating that high numbers of specific liver T RM cells were associated with viral control [58]. However, accumulation of intrahepatic CD8 + CD103 + perforin + T cells has been observed in cases of autoimmune hepatitis, particularly in indetermined pediatric acute liver failure [106]. These findings suggest that liver T RM cells could also have a pathogenic function.…”
Section: Liver T Rm Cell Immune Responses To Infectionmentioning
confidence: 95%